Available phosphorus requirement of juvenile Asian red-tailed catfish (Hemibagrus wyckioides) - Chenghao Yang; Wenhao Long; Weijia Cai; Yaozhengtai Zhang; Xinping Li; Yi Hu; Lei Zhong; Jihong Dai (Aquaculture Reports)
This study explored the optimal dietary available phosphorus (P) requirement for juvenile Asian red-tailed catfish (Hemibagrus wyckioides). Five isonitrogenous (42.00 %) and isolipidic (9.00 %) diets with monocalcium phosphate supplementation levels of 0.00 %, 0.75 %, 1.50 %, 2.25 %, and 3.00 % (namely P0, P0.75, P1.5, P2.25, and P3) were fed to fish for 56 d. Weight gain rate increased with phosphorus supplementation up to 2.25 % and then declined. The apparent digestibility coefficients (ADC) of phosphorus and calcium, as well as the phosphorus and calcium contents in the whole body and vertebrae, exhibited a positive correlation with dietary phosphorus levels, while the expression of intestinal genes related to phosphorus transport and metabolism showed a negative correlation with increasing dietary phosphorus levels. Using quadratic regression, the optimal phosphorus requirement was estimated at 0.87% based on weight gain and 0.99 % based on vertebrae phosphorus content. Whole body crude lipid content and serum total cholesterol was significantly lower in P1.5, P2.25, and P3 compared to the P0 and P0.75 group (P < 0.05). Liver lipid droplet volume and number were markedly reduced in P2.25 compared to the P0 group. Phosphorus deficiency resulted in stunted growth, reduced bone mineralization, and increased lipid accumulation in whole-body tissue and the liver. These findings provide practical guidance for phosphorus supplementation in H. wyckioides aquaculture, optimizing growth and bone mineralization while minimizing excess phosphorus in feeds.